2019
DOI: 10.1111/nhs.12626
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances and related factors among nurses

Abstract: The aim of this study was to describe patterns and potential risk factors for sleep disturbances, including that of sleep apnea, among Thai registered nurses. A descriptive, cross-sectional design was implemented. A sample of 233 registered nurses was recruited from 10 nursing departments from a tertiary hospital. Participants completed a one-time, self-report questionnaire and a 1 week-long sleep diary. Descriptive and logistic regression statistics were used for the analysis. Approximately 76% of nurses slep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
3
19
2
3
Order By: Relevance
“…The mean total sleep time in our study was overall consistent with findings from other studies. 16 , 18 The prevalence of SSD in our study is very close to the survey in Brazil, which demonstrated that 48.6% of nurses had SSD, 17 but is much lower than in Thailand, in which they found about 76% nurses slept less than 7 hours. 15 , 16 This gap may be due to the differences of the healthcare systems and characteristics of participants.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The mean total sleep time in our study was overall consistent with findings from other studies. 16 , 18 The prevalence of SSD in our study is very close to the survey in Brazil, which demonstrated that 48.6% of nurses had SSD, 17 but is much lower than in Thailand, in which they found about 76% nurses slept less than 7 hours. 15 , 16 This gap may be due to the differences of the healthcare systems and characteristics of participants.…”
Section: Discussionsupporting
confidence: 83%
“… 16 , 18 The prevalence of SSD in our study is very close to the survey in Brazil, which demonstrated that 48.6% of nurses had SSD, 17 but is much lower than in Thailand, in which they found about 76% nurses slept less than 7 hours. 15 , 16 This gap may be due to the differences of the healthcare systems and characteristics of participants. For example, 57.7% of Thai nurses in the studies were single, 15 , 16 while only 31.25% nurses were not married in our sample.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“… 10 A number of cross-sectional studies of workers in specific occupations, such as nurses, have suggested a relationship between night and shift work and depressive symptoms. 11 12 However, a 10-year observational cohort study showed contrary evidence, wherein being engaged in present or previous night work was not associated with sickness absence due to mental health problems. 13 Some observational studies reported that there was no significant association between night/shift work and depression.…”
Section: Introductionmentioning
confidence: 99%